2018
DOI: 10.3126/jucms.v6i2.22473
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Lesions in Urinary Bladder- A Histopathological Study

Abstract: Introduction: The lesions of urinary bladder both non-neoplastic and neoplastic pose a common source of both morbidity and mortality. An accurate diagnosis of these lesions requires cystoscopy which allows a direct visualization of the bladder mucosa and biopsies of suspected lesions. Urinary bladder cancer is sixth most common cancer worldwide and represents a heterogeneous group of neoplasms. The current study aimed to study the different bladder lesions and its clinical features to detect it in early stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 0 publications
4
8
0
Order By: Relevance
“…In non-invasive papillary urothelial neoplasia, predominant type was PUCLG (55.33%) followed by PUCHG (14%), papillomas (13%) and PUNLMP (3.34%). This was in concordance with studies performed by Laishram RS et al [22] who showed maximum number of PUCLG (53.9%) followed by PUCHG (37.6%), papillomas (7.7%) and PUNLMP (3.9%) and Thapa et al [17] who observed high prevalence of PUCLG (50%) followed by PUCHG (30.36%), PUNLMP (10.71%) and papilloma (9%).Our study was also in concordance with Shah P et al [23] who observed maximum no. of non-invasive PUCLG (47.36%) in prevalence of PUCLG (50%) followed by PUCHG (30.36%), PUNLMP (10.71%) and papilloma (9%).Our study was also in concordance with Shah P et.…”
Section: Discussionsupporting
confidence: 92%
“…In non-invasive papillary urothelial neoplasia, predominant type was PUCLG (55.33%) followed by PUCHG (14%), papillomas (13%) and PUNLMP (3.34%). This was in concordance with studies performed by Laishram RS et al [22] who showed maximum number of PUCLG (53.9%) followed by PUCHG (37.6%), papillomas (7.7%) and PUNLMP (3.9%) and Thapa et al [17] who observed high prevalence of PUCLG (50%) followed by PUCHG (30.36%), PUNLMP (10.71%) and papilloma (9%).Our study was also in concordance with Shah P et al [23] who observed maximum no. of non-invasive PUCLG (47.36%) in prevalence of PUCLG (50%) followed by PUCHG (30.36%), PUNLMP (10.71%) and papilloma (9%).Our study was also in concordance with Shah P et.…”
Section: Discussionsupporting
confidence: 92%
“…The male to female ratio from various studies highlight the association between bladder neoplasms and increased m a l e s u s c e p t i b i l i t y. P re s e n t s t u dy a l s o h a d m a l e preponderance with M: F ratio of 4:1. However, the range of this ratio is very wide as observed in various studies ranging from least being observed is 2.29:1 in study by Shah PY et al [16] to highest observed ratio of 5.25:1 in study by Srikoustubah [17] et al Smoking had a predominant role in development of bladder cancer in males along with other factors such as occupational carcinogens like aniline dyes (particularly benzidine and β-naphthylamine), auramines, phenacetin and cyclophosphamide. Schistosoma haematobium is also thought to be pathogenetically related to urothelial (and squamous cell) carcinoma of bladder Incidence among females could be explained by use of smokeless tobacco in the forms like gutkha, paan, khaini, tobacco or surti.…”
Section: Discussionmentioning
confidence: 85%
“…Urinary bladder lesions are responsible for significant morbidity and mortality [1] . urothelial carcinoma is the 6 th most common cancer worldwide [2] . Cystoscopy is the primary investigation to diagnose bladder lesion and rule out bladder cancers in suspected cases.…”
Section: Discussionmentioning
confidence: 99%
“…histopathological examination of bladder biopsies not only gives the diagnosis but also provides information to the Urologist to plan treatment. Diagnosis and monitoring of bladder lesions are made by combining cystoscopic and histopathological findings [2,3] . 147 bladder biopsies were analyzed in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation